Predicting the Severity of Acute Appendicitis of Young Children (<3 Years Old): Development and Assessment of a New Prediction Nomogram - Chen, Yang; Wang, Zhiyong; Xiao, Dong; Zeng, Hongwu; Ma, Xiaopeng (Frontiers in Pediatrics, 2021)
Objective There is a lack of assessment methods of acute appendicitis in little children. The purpose of this study was to develop and internally validate a nomogram for predicting the severity of acute appendicitis of young children (<3 years old). Methods We develop a prediction model based on a training dataset of 121 patients (<3 years old) with acute appendicitis. Admission information was collected between January 2010 and January 2021, which contained demographic characteristic, laboratory examinations, treatment and pathology type, etc. Logistic regression analysis was used to identify independent risk factors and establish the predictive model. C-index and calibration curves were applied to evaluate the performance of the nomogram. Then corrected C-index was calculated to conduct internal verification by using the bootstrapping validation. Decision curve analysis determined clinical application of the prediction model. Results Predictors contained in the prediction nomogram included weight for age, onset time (from developing symptoms to hospital), admission temperature, leukocyte count, neutrophil ratio, and total bilirubin. Logistic regression analysis showed that weight for age(X1) <-2.32SD (P=0.046), onset time(X2) >2.5 days (P=0.044), admission temperature(X3) >38.5℃ (P=0.009), leukocyte count(X4) >12.185*109/L (P=0.045), neutrophil ratio(X5) >68.7% (P=0.029), and total bilirubin(X6) >9.05umol/L (P=0.035) were found to be significant for predicting the severity of appendicitis. The logistic regression equation was logit(P)=-0.149X1+0.51X2+1.734X3+0.238X4+0.061X5+0.098X6-75.229. C-index of nomogram was calculated at 0.8948(95%Cl:0.8332-0.9567) and it still was 0.8867 through bootstrapping validation. Decision curve analysis showed that when the threshold probability ranged from 14% to 88%, there is a net benefit of using this prediction model for severity of appendicitis in little children. Conclusion This novel nomogram incorporating the weight for age, onset time, admission temperature, leukocyte count, neutrophil ratio, and total bilirubin could be conveniently used to estimate the severity of appendicitis of young children (<3 years old) and determine appropriate treatment options in time.